Cellulo: Versatile Handheld Robots for Education - Özgür, Ayberk; Lemaignan, Séverin; Johal, Wafa; Beltran, Maria; Briod, Manon; Pereyre, Léa; Mondada, Francesco; Dillenbourg, Pierre (2017 12th ACM/IEEE International Conference on Human-Robot Interaction (HRI, 2017)
In this article, we present Cellulo, a novel robotic platform that investigates the intersection of three ideas for robotics in education: designing the robots to be versatile and generic tools; blending robots into the classroom by designing them to be pervasive objects and by creating tight interactions with (already pervasive) paper; and finally considering the practical constraints of real classrooms at every stage of the design. Our platform results from these considerations and builds on a unique combination of technologies: groups of handheld haptic-enabled robots, tablets and activity sheets printed on regular paper. The robots feature holonomic motion, haptic feedback capability and high accuracy localization through a microdot pattern overlaid on top of the activity sheets, while remaining affordable (robots cost about EUR 125 at the prototype stage) and classroom-friendly. We present the platform and report on our first interaction studies, involving about 230 children.